The Plagiarism Awareness of University’s Students in Writing Research Proposal - Hairunnisa Hairunnisa; Norlinda Norlinda; Nur Yulia Latifah; Melisa Khairaini; Salwa Ramadhani; Saripah Banseng; Ciptro Handrianto (English Language Education Department, Universitas Kristen Duta Wacana (UKDW), Yogyakarta, Indonesia, 2023)
This study aimed to investigate the students' understanding and awareness of plagiarism in writing proposal. This study also investigated their reasons doing plagiarism in academic writing. A qualitative research method was used in this study by using interview for data collection techniques based on phenomenological research. The participants of this study were four students in the sixth semester in the English department at one of public universities in Banjarmasin. The study showed that students were aware of the act of plagiarism. They did plagiarism because of several factors, namely, laziness, wanting to finish quickly, and being pressured by circumstances. The study concluded that students needed to warn from the beginning related to the cause and impact of plagiarism for their future career. It`s not only bad for themselves but also harm others. The students should be actively involved in writing classes to express their own ideas and it can help them in proposal writing.